The immune microenvironment in tumors: focus on canine and feline spontaneous neoplasms - Rizzi, Maddalena; D’Annunzio, Giulia; Tugnoli, Chiara; Sarli, Giuseppe; Muscatello, Luisa Vera (Frontiers in Veterinary Science, 2025)
Companion animals develop spontaneous tumors with biological and immunological features closely resembling human cancers. The tumor microenvironment (TME), particularly its immune infiltrates, plays a pivotal role in tumor progression and immune evasion. This review summarizes current knowledge on the composition and function of immune cells (including T cells, B cells, macrophages, dendritic cells, neutrophils, and mast cells) in the TME of canine and feline tumors. A better understanding of these mechanisms may aid in identifying prognostic biomarkers and novel immunotherapeutic targets in both veterinary and human oncology.